2021
DOI: 10.3390/ijms22031279
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Brain Injury Increases Cells’ Production of Cystathionine β-Synthase and Glutamine Synthetase, but Reduces Pax2 Expression in the Telencephalon of Juvenile Chum Salmon, Oncorhynchus keta

Abstract: The considerable post-traumatic brain recovery in fishes makes them a useful model for studying the mechanisms that provide reparative neurogenesis, which is poorly represented in mammals. After a mechanical injury to the telencephalon in adult fish, lost neurons are actively replaced due to the proliferative activity of neuroepithelial cells and radial glia in the neurogenic periventricular zone. However, it is not enough clear which signaling mechanisms are involved in the activation of adult neural stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…Studies on the medaka, Oryzias latipes, and the zebrafish, Danio rerio, have also shown that, within proliferative populations in the optic tectum, aNSCs are indeed NE-like stem/progenitor cells, but not RG cells [20,21]. Similar results were obtained in other studies, in particular, on the optic tectum [22] and telencephalon [23]. The study of the lateral zebrafish pallium revealed a population of adult NE cells [24,25] maintained from an early to various postembryonic stages of ontogenesis.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Studies on the medaka, Oryzias latipes, and the zebrafish, Danio rerio, have also shown that, within proliferative populations in the optic tectum, aNSCs are indeed NE-like stem/progenitor cells, but not RG cells [20,21]. Similar results were obtained in other studies, in particular, on the optic tectum [22] and telencephalon [23]. The study of the lateral zebrafish pallium revealed a population of adult NE cells [24,25] maintained from an early to various postembryonic stages of ontogenesis.…”
Section: Introductionsupporting
confidence: 84%
“…In trout, RG cells often formed clusters separated by immunonegative regions in the marginal zone (Figure 2B,D). The presence of GS+ RG cells was revealed also in other fish species such as Apteronotus albifrons [34], the zebrafish [67], and the chum salmon O. keta [23]. Tectal glia have been described as "tanycytes" from the ocean sunfish, Mola mola [68]; however, cells of this type in the goldfish, Carassius auratus, were referred to as "radial glia" [69], and in L. macrochirus and P. nebulifer as "ependymoglia" [70].…”
Section: Expression Of Glutamine Synthetase In the Tectummentioning
confidence: 99%
“…The drug treatment also diminished the sTBI-mediated increase in brain L-Cystat and normalized the level of SAH. Although obtained in a fish model of TBI, it was found that head trauma causes an increase in the expression of the L-Cystat synthesizing enzyme (L-cystathione-β-synthase) in the post-injured brain [ 39 ], thereby possibly explaining the 1.9 and 1.7-fold increase in L-Cystat we found in sTBI rats at 2 and 7 days post-impact, respectively. On the other hand, since the precursor of GSH biosynthesis (L-cysteine) originates from the enzymatic scission of L-Cystat, the increased levels of L-Cystat following sTBI may be causative of a decreased rate of GSH biosynthesis due to decreased L-cysteine availability.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroepithelial cells play an essential role in mammalian embryonic neurogenesis, while glial stem cells are the main source of neurons at the postembryonic stages of development [27]. In contrast to mammals, neuroepithelial-like (NE) stem/progenitor cells are present in the brain of fish throughout life [27][28][29].…”
Section: Introductionmentioning
confidence: 99%